MicroRNAs in skeletal muscle and their regulation with exercise, ageing, and disease - Zacharewicz, Evelyn; Lamon, Severine; Russell, Aaron P. (Frontiers in Physiology, 2013)
Skeletal muscle makes up approximately 40% of the total body mass, providing structural support and enabling the body to maintain posture, to control motor movements and to store energy. It therefore plays a vital role in whole body metabolism. Skeletal muscle displays remarkable plasticity and is able to alter its size, structure and function in response to various stimuli; an essential quality for healthy living across the lifespan. Exercise is an important stimulator of extracellular and intracellular stress signals that promote positive adaptations in skeletal muscle. These adaptations are controlled by changes in gene transcription and protein translation, with many of these molecules identified as potential therapeutic targets to pharmacologically improve muscle quality in patient groups too ill to exercise. MicroRNAs (miRNAs) are recently identified regulators of numerous gene networks and pathways and mainly exert their effect by binding to their target messenger RNAs (mRNAs), resulting in mRNA degradation or preventing protein translation. The role of exercise as a regulatory stimulus of skeletal muscle miRNAs is now starting to be investigated. This review highlights our current understanding of the regulation of skeletal muscle miRNAs with exercise and disease as well as how they may control skeletal muscle health.